A apatia societal e o desenvolvimento dos municípios paranaenses: externalidades, correlações e possíveis impactos - Santos, Suzane Raquel Guerra (2018)
The societal participation is a participative process in which the citizens participate actively in the decision taking of the public administration. Because it is an utopic process, in fact people have been living the societal apathy, which is the lack of the society interest in the participation, thus, arising the feeling that nothing can be done to change and improvement of the political system, allowing the authorities to feel comfortable to act the way they want, due the lack of the society supervision before the decisions made. Therefore, the study assumes that the societal apathy brings negative externalities to the local and regional development, it establishes as suppositions that the societal participation mediated by the municipal election participation index (partDI), as input of the Democratization Index (DI) is directly proportional to the Municipal Output IPARDES Index (MOII)and the municipalities with a lower DI have a higher societal apathy, consequently, a lower development (MOII).Hence, the main goal of the research is to analyze the relations among the societal apathy, measured by the DI and its components: participation and competition, with the local development. The specific goals are: to calculate the DI and its components (inputs): participation and competition of the Paraná municipalities; to study the possible correlations among the participation index as a DI component, as well as the DI correlation itself between the development index of the Paraná municipalities, measured by the MOII; to identify possible externalities resulting from the relation among the participation and democratization indexes and the Paraná municipalities MOII. Consequently, we intend to build a relevant study, working with current variables and connecting important themes in order to solve local and regional society problems. For this purpose, we seek to answer: which are the main possible impacts caused by the societal apathy and their externalities on the development of the Paraná municipalities, considering the electoral democratization index of the respective municipalities? Methodologically, the study is based on applied research, with quantitative approach; in terms of the purpose, it is exploratory and described, ex-post facto analyzed, and with procedures of bibliographic and documental nature. As results, it was possible to identify, by using correlational analysis among the indexes observed: electoral participation (DI) and the sub-index participation (partDI) with the MOII, as explanatory variables, a very low correlation coefficient, denoting the inexistence of a statistical correlation among the observed data. In conclusion, the societal apathy do not interfere in the local and regional development of the Paraná municipalities.